Reasons for the election and preferences of the medical specialty in general practitioners of Peru - Alarcon-Ruiz, Christoper A. (2020)
Objective: to describe the reasons that influence the choice of medical specialty in general physicians in Peru, and to calculate the applicants and vacancies in the national medical residency exam in 2018. Materials and methods: descriptive cross-sectional study in general physicians who attended an event that aimed to inform about medical specialties, carried out by the Peruvian Medical College. During this event, a self-applied questionnaire was distributed to collect the variables of interest. The statistical analyzes were performed with the Stata v.14 program. Results: surveys of 298 participants wereanalyzed, of which 54.4% were women, 46.3% had less than 28 years old, 59.8% studied their undergraduate studies in Lima, and 52.3% completed their career between 2014-2016. 49.7%, 46.6%, and 3.7% preferred choosing a surgical specialty, clinic, and some other, respectively. The reasons considered important or very important to choose a specialty were: the high probability of getting a job (98.7%), having intellectual challenges (94.9%), see interesting cases (93.2%), and have good economic income (90.8%). Plastic surgery and dermatology were the specialties with greatest number of applicants for each vacant, while family medicine and internal medicine had less applicants than vacancies. Conclusions: Peruvian physicians consider economic and academic reasons as the most important ones, when choosing a specialty, in a context where primary care specialties had few applicants. This allows us to better understand the process behind choosing and specialty, adequately inform to the physicians about the specialties available, and promote strategies to increase the interest of doctors in specialties needed in the country.